The roles of residential greenness in the association between air pollution and health: a systematic review. (24th August 2021) - Son, Ji-Young; Choi, Hayon Michelle; Fong, Kelvin C; Heo, Seulkee; Lim, Chris C; Bell, Michelle L
Abstract: While a growing body of literature suggests beneficial impacts of greenness on several health outcomes, relatively few studies have examined greenness as an effect modifier to impacts of air pollution on health outcomes, and results from the existing studies are inconclusive. We performed a comprehensive, systematic review of previous literature on greenness as a potential effect modifier for associations between particulate matter air pollution and health. After initial screening of 7814 studies, we identified 20 eligible studies. We summarized findings on study characteristics based on several criteria: health outcome, air pollution exposure, source of air pollution data, study location, study period, and median year of the study period. We evaluated characteristics of effect modification by greenness on air pollution and health associations based on the number of greenness metrics applied, type of greenness metric (e.g. normalized difference vegetation index, land use), data source for greenness, and spatial resolution and buffer size. We also summarized evidence for effect modification by greenness based on strength and direction of evidence for each study and overall evidence of effect modification by greenness by several study characteristics. Our systematic review showed that only a limited number of studies have been conducted on greenness as an effect modifier for air pollution-health associations. We found differences in several study characteristics such as greenness assessment (e.g. greenness metrics applied, spatial resolution, and data sources) across studies. Collectively, the studies provide suggestive evidence for the hypothesis that areas with high greenness have lower impacts of air pollution on health, although some studies reported inconsistent findings. The findings from our review provide valuable knowledge on how greenness affects associations between air pollution and health and could help identify critical areas for future study.